Ahead Of The Game - Ledbetter, Suzann (New York MIRA, 2004)
When Zoey Jones' life is downsized by a divorce and a pink slip, she returns to her hometown. As if keeping her rebellious daughter in line and working overtime tending bar isn't enough, her old flame, cop Hank Westlake, charges Zoey's father with murder. Original.
Keywords: Missouri -- Divorced women